2009
DOI: 10.1249/jsr.0b013e3181b7ee5f
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Elbow Injuries in Youth Baseball Pitchers

Abstract: There is concern among sports medicine practitioners that the number of youth baseball pitchers with elbow injuries appears to be increasing. Research points to overuse as the principle risk factor. The risk of elbow pain in youth pitchers is correlated with the number of pitches thrown in a game and in a season. Adolescents who competitively pitch more than 85 pitches per game, more than 8 months out of a year, or with arm fatigue are several times more likely to require elbow surgery. Poor pitching mechanics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
126
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(130 citation statements)
references
References 24 publications
2
126
1
1
Order By: Relevance
“…8 Although injury prevention programs have been instituted over the past decade to protect adolescent athletes from injury, these programs have yet to yield a significant decline in injury rates. 10,11 Interestingly, this study did not show a significant difference in the yearly timing of UCLR. One could postulate that pitchers are at greater risk for injuries during the beginning of the season, as they have not yet returned to game shape, but this does not appear to be accurate based on this study.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…8 Although injury prevention programs have been instituted over the past decade to protect adolescent athletes from injury, these programs have yet to yield a significant decline in injury rates. 10,11 Interestingly, this study did not show a significant difference in the yearly timing of UCLR. One could postulate that pitchers are at greater risk for injuries during the beginning of the season, as they have not yet returned to game shape, but this does not appear to be accurate based on this study.…”
Section: Discussioncontrasting
confidence: 53%
“…Other studies have shown that risk factors for sustaining an initial UCL tear include growing up in warm weather climates and pitching while fatigued (including pitching for multiple teams at a time, pitching more than 100 innings per season, pitching more than 9 months of the year, etc). 7,10 Interestingly, throwing breaking pitches at early ages has not been shown to correlate with UCL injuries, which is a common misconception among athletes, parents, and coaches. 10 The patients in this study did not routinely undergo elbow arthroscopy at the time of UCLR unless there was documented or suspected intra-articular pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pitchers who continue to throw when the arm is fatigued risk serious and possibly permanent injury to their muscles, ligaments, capsules, labra, and bones. 35 The scapula plays a critical role in the functioning kinetic chain of the upper extremity. The scapula is attached to the distal end of the clavicle by the broad acromioclavicular ligament and the 2 coracoclavicular ligaments that arise from the hooklike coracoid.…”
Section: Overload Causing Overuse Injury Of the Shoulder And Elbow Inmentioning
confidence: 99%
“…Moreover, the aUCL may be torn with acute upper extremity trauma, and is often torn in an acute elbow dislocation. Although this injury is relatively uncommon, it has clearly become a clinically significant problem, as highlighted by recent literature regarding the injury rate and reconstruction of the aUCL in adolescent athletes [2,4]. Finally, if the aUCL is attached primarily to the apophysis of the medial epicondyle there may be stability issues related to isolated medial epicondyle fractures.…”
Section: Introductionmentioning
confidence: 99%